Rural communities’ energy metabolisms in Portugal: Between territorial injustices and far-right populism - Batel, S.; Valquaresma, A.; Alba, M. (Journal of Rural Studies, 2024)
In the last decades, rural areas have been centerstage of a critical energy social sciences’ research agenda, as the local resistance to the injustices of the renewable energy transition has increased. At the same time, far-right populism and related rhetoric against migrants and minorities has been on the rise across the world, often making use of rural communities’ concerns and deprivations. However, the relations between far-right populism, its nationalist and anti-migrant rhetoric, and the renewable energy transition as experienced by rural communities have not often been examined. This paper aims to contribute to this area of research by exploring how two rural communities in Portugal – Graciosa in the Azores islands and Castelo de Vide in mainland Portugal – where votes for the far-right populist Portuguese party have increased in the last elections and where large-scale renewable energy infrastructures have been deployed or are planned, experience and make sense of these issues and relations between them. Interviews and focus groups with community members and key local stakeholders were conducted (N = 16 and N = 3 respectively, in each case study). Results show some similarities between the two rural areas in how they represent themselves as economically sacrificed territories that allow a good life to be lived, as well as on positionings in relation to the far-right populist Portuguese party; and also some differences regarding the politization of the renewable energy transition and its relationship with social diversity issues. We conclude by discussing the implications of these findings to rural planning and policymaking on the green transition.